(untitled) (Journal of The Colloquium for Information Systems Security Education, 2025)
Industrial Cybersecurity is an emerging interdisciplinary field of study and practice. This paper presents the results of research and collaboration to create a data-supported and consensus-based curricular guidance document describing the knowledge needed of professionals in the field.